OntoCaimer: Towards an Ontological Model to Support the Care of Patients with Alzheimer's Disease - Lasso-Arciniegas, Laura-Daniela; Pardo-Calvache, César-Jesús; Mazo, Raúl (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The World Health Organization declared Alzheimer's disease and its care a global public health priority in 2021 due to its complexity and development, which affects the patient and their caregiver. Alzheimer's symptoms worsen daily, so the patient must have 24/7 care; between responsibilities, the caregiver must deal with arduous tasks, from bathing the patient to managing the behavioral symptoms. By carrying out a systematic mapping, it was possible to identify that, despite the profuse information about Alzheimer's and its care, there is no concise source of information that allows the development of integrated systems that support the care of patients with Alzheimer's. This paper is presented OntoCaimer, which is an ontology that synthesizes the recommendations and preventive actions for most of the symptoms of the different stages of Alzheimer's. OntoCaimer integrates concepts related to sensors, actuators, and measurement, making it possible to use it as a basis for the development of systems that support patient care digitally through alerts or with the use of actuators to support patient care. OntoCaimer allows automating a group of variables associated with recommendations or preventive actions such as weight, environment, and feeding schedules, among others, which would support patient care, reduce caregiver tasks, and serve as a knowledge base for the scientific community and the development of systems that implement electronic systems or simulations before their implementation.